Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Melalui Media Pembelajaran Interaktif Articulate Storyline Pada Materi Peluang - Fregita Habuke; Evi Hulukati; Khardiyawan A.Y Pauweni (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
This study aims to improve students' mathematical problem-solving ability using articulate storyline interactive learning media in SMP N 2 Telaga Biru. This research is a Classroom Action Research. The subjects are grade VIII students consisting of 20 students. The data collection techniques include observation and test. The data analysis includes data analysis of teacher observations, student observations, and analysis of problem-solving ability test results. The research procedure includes action planning, implementation, observation, and reflection. This research was conducted in stages with two cycles, namely cycle I and cycle II. The tests and observations obtained from the two cycles showed that students' mathematical problem-solving ability increased in cycle II.